2020
DOI: 10.3390/cleantechnol2030023
|View full text |Cite
|
Sign up to set email alerts
|

Waste Recovery through Thermochemical Conversion Technologies: A Case Study with Several Portuguese Agroforestry By-Products

Abstract: Agroforestry waste stores a considerable amount of energy that can be used. Portugal has great potential to produce bioenergy. The waste generated during agricultural production and forestry operation processes can be used for energy generation, and it can be used either in the form in which it is collected, or it can be processed using thermochemical conversion technologies, such as torrefaction. This work aimed to characterize the properties of a set of residues from agroforestry activities, namely rice husk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 114 publications
(124 reference statements)
2
11
0
Order By: Relevance
“…The mass loss presented an average value of 78.31 ± 1.00%. The values verified in the mass loss are in agreement with the values presented in previous works, such as those by Tag et al (2016) or [23,33]. The values presented in the referred works are included in the range 75-80% for process temperatures of 400 • C and equivalent residence time.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The mass loss presented an average value of 78.31 ± 1.00%. The values verified in the mass loss are in agreement with the values presented in previous works, such as those by Tag et al (2016) or [23,33]. The values presented in the referred works are included in the range 75-80% for process temperatures of 400 • C and equivalent residence time.…”
Section: Resultssupporting
confidence: 89%
“…However, given the considerable volumes of biomass produced annually throughout the country, it is very difficult to collect and use it, given the dispersion of wine production throughout the territory, which is usually abandoned, or else eliminated by burning the leftovers [29,30]. Despite the recognized properties as a fuel, previously reported in several works, such as those by Duca (2020), where several characterizations of materials and different forms of energy recovery, such as anaerobic digestion, pyrolysis or gasification, are presented, still exists a deep lack of knowledge concerning creating value chains using these materials and about the best options to manage the amounts yearly generated [31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…The PAS presented between 75.35 and 77.95% of volatile matter, values close to those observed for others lignocellulosic biomass (BARBOSA et al, 2019;NUNES et al, 2020). The high volatiles content is an important characteristic for biomass application in pyrolysis processes, because it indicated that a large fraction of biomass is converted into steam and gas when heated, which leads to the possibility of high yield of bio-oil .…”
Section: Resultssupporting
confidence: 80%
“…The characterization results of dry basis biomass (Table 1) indicated suitable values for thermochemical conversion processes: low moisture and ash content, high volatiles content, and a moderate bulk density. The moisture reduces the HHV and inhibit ignition because an amount of energy is used to dry the biomass (SAMADI et al, 2020;NUNES et al, 2020). In addition, high moisture content can damage the storage, causing fungal proliferation and material degradation, as well as increasing transport costs.…”
Section: Resultsmentioning
confidence: 99%
“…The laboratory procedure used in the present study was similar to the one used for the carbonization of various types of biomass, and previously described by Nunes et al [45]. The tires collected were divided into five groups composed by 5 samples each, with approximately 750 g of material.…”
Section: Laboratorial Torrefaction and Carbonization Proceduresmentioning
confidence: 99%